PERMASALAHAN GURU BAHASA INGGRIS DALAM MENGIMPLEMENTASIKAN KURIKULUM 2013 DI SLTA KABUPATEN TANAH DATAR - SUSWATI HENDRIANI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
The research is conducted based on the fact that Senior high school English teachers of Tanah Datar Regency face problems in implementing curiculum 2013.The research is aimed at finding out the problems of the teachers related to the implementation of the Curriculum. Therefore, a qualitative research method was applied. To collect the data of the research, interview technique was used. To analyze the colled data, interactive model of analysis as proposed by Miles and Huberman was used. The results of the research show that there were two types of the problems that the teachers faced in implementing the new Curriculum, those deriving from the teachers themsevels, and those deriving from others, like government, students and facilities. Kata kunci: permasalahan, guru, bahasa Inggris, implementasi, kurikulum 2013